Development of fabrication process for embedded structure in multi-layer low temperature co-fired ceramics (LTCC) using sacrificial carbon by process modelling and simulation - Tan, Yeow Meng (2013)
The most promising method to realise the necessary embedded structure in Low Temperature Co-fired Ceramics (LTCC) is by employing carbon sacrificial material. Process characterisation with respect to carbon burn-off, particularly under embedded condition for dimensional accuracy, is hitherto yet to be established. In this investigation, physical phenomena were identified for carbon burn-off for embedded structure fabrication. A chemical reactions mass transport model with LTCC sintering pore evolution was developed for process characterisation. Competing kinetics were observed and analysed for various firing profiles, including those with incomplete carbon burn-off. The process model was employed in a practical application for distortion minimisation for a large embedded air cavity. The minimised cavity deformation through process optimization is a significant achievement. The process model has the potential to greatly reduce the time required for experimental trials, with improvement of product quality in terms of dimensional and shape consistency and tolerance.